Creolization and Empire: Creating Diversity and Navigating Social Change in Portuguese West Africa - Havik,Philip J. (2022)
Abstract The twin phenomena of the formation of Creole strata and societies and cultural creolization have dominated debates on the uniqueness of Caribbean contexts and universalist notions of cross-cultural interaction at a global level. These analytical threads are integrated into a study of processes of creolization and acculturation in their multiple forms in areas of (former) Portuguese presence in West Africa. Deeply entangled with four centuries of the Atlantic slave trade and the rise and fall of the colonial state, the remarkable diversity of cross-cultural encounters in empire is addressed here for Cabo Verde, Guinea-Bissau, São Tomé and Príncipe, and Angola.